Evaluation of Different Activity of Lactobacillus spp. against Two Proteus mirabilis Isolated Clinical Strains in Different Anatomical Sites In Vitro: An Explorative Study to Improve the Therapeutic Approach - Alessandra Fusco; Vittoria Savio; Adriana Chiaromonte; Alberto Alfano; Sergio D’Ambrosio; Donatella Cimini; Giovanna Donnarumma (Microorganisms, 2023)
Urinary tract infections (UTIs) and catheter-associated UTIs (CAUTIs) are the principal hospital-acquired infections. Between these, bacterial prostatitis is believed to be the leading cause of recurrent UTIs in men under 50 years of age and is often unresponsive to antibiotic treatment. Proteus mirabilis is more commonly associated with UTIs in these abnormalities, especially in patients undergoing catheterization. Lactobacillus spp. are an important component of the human microbiota and occur in large quantities in foods. Probiotics are proposed as an alternative to antibiotic therapy in the treatment of urinary tract infections. In addition to their ability to produce antimicrobial metabolites, they have immunomodulatory activity and do not cause side effects. For this reason, the combination of probiotic microorganisms and conventional drugs was considered. The aim of this work was to select the most active Lactobacillus strains against two clinical isolates of P. mirabilis on bladder and prostatic epithelium, potentially exploitable to improve the clinical management of UTIs.